Parental educational practices, emotional health and maternal sociodemographic variables: Nuclear and non-nuclear families - Nogueira, Sária Cristina [UNESP]; Rodrigues, Olga Maria Piazentin Rolim [UNESP]; Pereira, Veronica Aparecida (FapUNIFESP (SciELO), 2023)
Objective We compared parental educational practices and emotional health of 62 mothers of students from nuclear (G1) and non-nuclear families (G2). Method We used an inventory of parenting practices and scales for assessment of anxiety, stress and depression. Results G1 showed significantly higher means for Moral Behavior. Positive correlations between negative parenting educational practices and clinical indicators for maternal emotional health were perceived in both groups and more significantly for G2. Younger mothers in G1 indicated more signs of state anxiety and for G2 the lower socioeconomic level indicated more signs of stress and trait anxiety and less depression. Conclusion The data can contribute to the planning of interventions.
Práticas educativas parentais, saúde emocional e variáveis sociodemográficas maternas: famílias nucleares e não nucleares
Keywords: Families; Maternal behavior; Mental health